2006
DOI: 10.1056/nejmoa065061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramipril on the Incidence of Diabetes

Abstract: Among persons with impaired fasting glucose levels or impaired glucose tolerance, the use of ramipril for 3 years does not significantly reduce the incidence of diabetes or death but does significantly increase regression to normoglycemia. (ClinicalTrials.gov number, NCT00095654 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 633 publications
(116 citation statements)
references
References 24 publications
4
109
1
2
Order By: Relevance
“…A number of previous studies have reported beneficial metabolic effects of ACE inhibitors or angiotensin II receptor antagonists on insulin secretion, insulin action as well as on overall glucose metabolism in patients with T2D (5,6). In support of this, large-scale randomised prospective trials have reported a decreased incidence of T2D or leading to regression of impaired fasting glucose levels or impaired glucose tolerance to normoglycaemia by ACE inhibitors and angiotensin receptor blockers (ARBs), as primary or secondary outcomes (7,8). Studies on the use of bioactive peptides in diabetic patients are limited, and only a few studies have evaluated the effect of probiotics on specific elements of the metabolic syndrome (MS) in non-diabetic adolescents and adults (9,10,11).…”
Section: Introductionmentioning
confidence: 75%
“…A number of previous studies have reported beneficial metabolic effects of ACE inhibitors or angiotensin II receptor antagonists on insulin secretion, insulin action as well as on overall glucose metabolism in patients with T2D (5,6). In support of this, large-scale randomised prospective trials have reported a decreased incidence of T2D or leading to regression of impaired fasting glucose levels or impaired glucose tolerance to normoglycaemia by ACE inhibitors and angiotensin receptor blockers (ARBs), as primary or secondary outcomes (7,8). Studies on the use of bioactive peptides in diabetic patients are limited, and only a few studies have evaluated the effect of probiotics on specific elements of the metabolic syndrome (MS) in non-diabetic adolescents and adults (9,10,11).…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, angiotensin-converting enzyme inhibitors and angiotensin receptor blockers are associated with a reduction in the incidence of new-onset diabetes among patients with essential hypertension [107]. A notable exception was the Diabetes Reduction Assessment with Ramipril and Rosiglitazone Medication (DREAM) in which ramipril did not prevent the progression to diabetes in subjects with IGT or impaired fasting glucose [108]. However, in support of the hypothesis that angiotensin-converting enzyme inhibitors might protect against the development of diabetes, the rate of regression to normoglycaemia was increased by rampiril.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…In the ramipril treatment arm of the DREAM study [64], no reduction in the appearance of DM was observed, although there was a slight but statistically significant normalization of the glycemia. These data are in contrast to the above-mentioned benefits regarding blocking of the angiotension-renin system, albeit dealing with different populations at high risk, and of low risk in the case of the DREAM study.…”
Section: Prevention Of the Metabolic Syndromementioning
confidence: 99%